2020
DOI: 10.1007/s12471-020-01432-y
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac telerehabilitation as an alternative to centre-based cardiac rehabilitation

Abstract: Multidisciplinary cardiac rehabilitation (CR) reduces morbidity and mortality and increases quality of life in cardiac patients. However, CR utilisation rates are low, and targets for secondary prevention of cardiovascular disease are not met in the majority of patients, indicating that secondary prevention programmes such as CR leave room for improvement. Cardiac telerehabilitation (CTR) may resolve several barriers that impede CR utilisation and sustainability of its effects. In CTR, one or more modules of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
52
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 51 publications
1
52
0
5
Order By: Relevance
“…Taken together our results support that telerehabilitation is a viable alternative or supplement to conventional rehabilitation, as it supports patient motivation. As such, our results are in line with the general consensus in the literature stating that TR is a well-accepted, safe, and effective alternative or supplement to CR ( Anderson et al, 2017 ; Brouwers et al, 2020 ; Frederix et al, 2015 ; Piotrowicz, 2017 ; Spindler et al, 2019 ).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Taken together our results support that telerehabilitation is a viable alternative or supplement to conventional rehabilitation, as it supports patient motivation. As such, our results are in line with the general consensus in the literature stating that TR is a well-accepted, safe, and effective alternative or supplement to CR ( Anderson et al, 2017 ; Brouwers et al, 2020 ; Frederix et al, 2015 ; Piotrowicz, 2017 ; Spindler et al, 2019 ).…”
Section: Discussionsupporting
confidence: 90%
“…Telerehabilitation (TR) is increasingly adopted as a means to overcome some of these barriers ( Brouwers et al, 2020 ; Knudsen et al, 2019 ). TR entails the delivery of rehabilitation via information and communication technologies over distance ( Brennan et al, 2010 ), and is used increasingly on a global scale, especially so during the COVID-19 pandemic.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…TR is defined as rehabilitation using information and communication technologies for delivery of rehabilitation activities [13]. Reviews describing TR in cardiac patients highlight the findings that TR has been shown to be as effective as conventional rehabilitation [14,15]. A review of the literature showed no studies of TR programs for AF patients that included monitoring parameters such as electrocardiography (ECG), steps, sleep, blood pressure, pulse, and weight.…”
Section: Introductionmentioning
confidence: 99%
“…The review article by Brouwers et al. in this issue outlines the numerous advantages of CTR [ 6 ]. As the authors point out, an initial centre-based introduction and evaluation appears appropriate, from both a safety and a psychological standpoint.…”
mentioning
confidence: 99%